Naevoid Psoriasis - D′Souza Paschal; Rathi Sanjay K; Joshi Arun; Khanna Neena (Wolters Kluwer Medknow Publications, 1998)
Naevoid psoriasis is a controversial entity and has often been used synonymously with psoriasiform inflammatory linear verrcous epidermal naevus (ILVEN) by some workers. Two patients having a linear psoriasiform eruption of 3 and 10 years duration respectively are reported. The winter aggravation of the lesions, the characteristic histology and favourable response to treatment led to the diagnosis of linear psoriasis. These features distinguished it from psoriasiform ILVEN which is a close differential diagnosis.